ASSESSING THE IMPACT OF DEMONETIZATION: A MACRO AND MICRO ANALYSIS - Trivedi, Arpit; Pillay, Tejaswini; Umarji, Sneha; Bhatele, Aarchi; Chaudhary, Ashwin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
November 7, 2021 announced the end of India's famous five-year demonetization operation. To assess how effective it is, the authors examined both the macro and micro effects. This research was done using secondary data from a poll of 120 regular men and women as well as data provided by the Reserve Bank of India. The survey's findings indicate that there is agreement on how to accomplish targets that include lowering interest rates, boosting cashless transactions, and decreasing corruption. The outcomes show that although the goals have been successfully met in most cases, some areas like micro-level corruption have not seen a substantial decline. People support a more systematic demonetization attempt as well. Policymakers are looking for ways to fight corruption at the national level. The study demonstrates how monetary policy can be utilized to successfully accomplish a number of objectives.